PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PT PUPUK ISKANDAR MUDA (Program Studi Administrasi Bisnis, 2022)
This study aims to examine the effect of motivation and discipline on the performance of employees of PT Pupuk Iskandar Muda. This research was conducted at PT Pupuk Iskandar Muda. The population in this study were employees of PT Pupuk Iskandar Muda totaling 558 people, and the determination of the sample using the